Mental Health, Coping And Social Skills For People Deprived Of Liberty - Arias Bravo, Paola Andrea; Almeida Salinas, Orlando; Sanchez Torres, Farid (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The research aims to implement a psychological intervention proposal that strengthens coping strategies and social skills of people deprived of liberty [PPL], inmates in the jail and penitentiary complex of Jamundí that contributes to their process of resocialization and prevention of disruptive and suicidal behaviors within the framework of the INPEC institutional program “Preservation of life”. The methodology has a mixed approach, sequential explanatory design, explanatory scope - cross-sectional exploratory. The sample: made up of 70 PPL selected by convenience. Expected results: Strengthening of coping strategies and life skills, reduction of disruptive behaviors.